Human Security Principles in Crowdsourcing Personal Data - Kharisma, Dona Budi; Hernoko, Agus yudha; Thalib, Prawitra; Oktafiyana, Oktafiyana (Faculty of Law, Universitas Pekalongan, 2024)
Personal data protection is fundamental because every individual's privacy is important. This article analyses related principles of human security in the context of processing personal data to ensure the safety of every personal data subject. The result of the paper shows that every effort in processing personal data must based on principles to ensure the fulfillment of human security principles. This article argues that crowdsourcing personal data often carried out in the digital era violates human security principles when impact losses are incurred to man.